SUSTAINABLE DEVELOPMENT OF COMMUNITY ENTERPRISES IN CHACHOENGSAO PROVINCE - Thaichareon, Thananchanok (Journal of MCU Nakhondhat, 2023)
The objectives of this research were: 1) to study the problems and obstacles in the sustainable development 2) to study the factors affecting the sustainable development and 3) to study the guidelines for sustainable development of community enterprises in Chachoengsao Province. The research was qualitative. To study from key informants such as chairman, community leaders, Chief of community and member group 20. By purposive sampling from representatives of outstanding community enterprises in 5 districts of Chachoengsao Province. The study instrument was a structured interview. Data analysis was performed using a description. The results found that: 1) the problems and obstacles in the sustainable development of community enterprises in such as lacking of knowledge and understanding in community enterprise management. Channel of Distribution were not diverse. Community enterprise members did not cooperate. The production of goods and services had a high cost, lack of good promotion and comprehensive from the government, working capital, technology used in production. 2) the factors affecting the sustainable development of community enterprises consisted of various factors, namely the cooperation of members families, the continuing activities, the development of the new generation, the community participation, relevant officials, government policy and marketing, and 3) the guidelines for sustainable development of community enterprises, including promoting the use of technology in operations, develop potential and knowledge of leaders and committees, cooperation, promote participation of people and communities. The government must support such as skills needs. The improving of laws and regulations and relevant laws should be updated. The marketing assistance from government, the work process improvement of community enterprises to be transparent and efficient and creating a basic welfare system for members.